An Ashkenazi Jewish woman presenting with favism. Issue 3 (25th February 2005) - Lim, F; Vulliamy, T; Abdalla, S H
Abstract : The case of a 44 year old Ashkenazi Jewish woman of Russian origin who presented with a typical clinical and haematological picture of favism is reported. There was initial difficulty in confirming glucose-6-phosphate dehydrogenase (G6PD) deficiency because the enzyme concentrations were normal at presentation, but later fell to a concentration compatible with heterozygosity for the Mediterranean type of G6PD deficiency. The diagnosis was also later confirmed by gene analysis. The reasons for the difficulties in the initial confirmation of the diagnosis and the normal G6PD enzyme activity at presentation are discussed.